Free Vastus Intermedius Muscle Flap: A Successful Alternative for Complex Reconstruction of the Neurocranium in Preoperated Patients. Issue 5 (July 2017) - Horn, Dominik; Freudlsperger, Christian; Berger, Moritz; Freier, Kolja; Ristow, Oliver; Hoffmann, Jürgen; Sakowitz, Oliver; Engel, Michael
Abstract : Abstract: The reconstruction of large cranial and scalp defects is a surgical and esthetic challenge. Single autologous tissue transfer can be insufficient due to the defect size and the anatomic complexity of the recipient site. Alloplastic patient-specific preformed implants can be used to recover hard tissue defects of the neurocranium. Nevertheless, for long-term success adequate soft tissue support is required. In this brief clinical study, the authors describe calvarian reconstruction in a 33-year-old patient with wound healing disorder after an initial resection of ependymoma. The patient suffered from osteonecrosis and wound breakdown in the fronto-parietal region. An alloplastic polymethylmethacrylate implant for hard tissue support was manufactured based on 3-dimensional visualization of a computed tomography scan. After the resection of remaining pathologic bone from earlier surgical procedures, the alloplastic implant was inserted to achieve functional coverage of the brain. Due to anatomic variation of donor site vessels during anterolateral thigh flap preparation, the authors performed a vastus intermedius free flap as a new muscular flap for craniofacial reconstruction. The authors achieved excellent functional and esthetic results. The muscular vastus intermedius free flap in combination with a split skin graft proves to be a new alternative to the anterolateral thigh flap for soft tissue reconstruction of the neurocranium.